Computer modeling of radiofrequency cardiac ablation: 30 years of bioengineering research. (February 2022) - González-Suárez, Ana; Pérez, Juan J.; Irastorza, Ramiro M.; D'Avila, Andre; Berjano, Enrique
Highlights: This is the first review exclusively focused on computer modeling applied to radiofrequency catheter cardiac ablation. We emphasize the historical context of the models, their contribution to the knowledge of the physics of ablation and their possible implications for clinical practice. We review the computer modeling studies intended to improve our knowledge of the biophysics of RFCA and those intended to explore new technologies. The most important technical details of the implementation of theoretical models are included. We point out some aspects not yet included in the state of the art which will surely require future studies to cover the existing gaps in our knowledge. Abstract: This review begins with a rationale of the importance of theoretical, mathematical and computational models for radiofrequency (RF) catheter ablation (RFCA). We then describe the historical context in which each model was developed, its contribution to the knowledge of the physics of RFCA and its implications for clinical practice. Next, we review the computer modeling studies intended to improve our knowledge of the biophysics of RFCA and those intended to explore new technologies. We describe the most important technical details of the implementation of mathematical models, including governing equations, tissue properties, boundary conditions, etc. We discuss the utility of lumped element models, which despite their simplicity are widely used by clinical researchers to provide a physical explanation of how RF power is absorbed in different tissues. Computer model verification and validation are also discussed in the context of RFCA. The article ends with a section on the current limitations, i.e. aspects not yet included in state-of-the-art RFCA computer modeling and on future work aimed at covering the current gaps.